Foucault, M. (2018). Histoire de la sexualité: Les aveux de la chair (Vol. IV). Paris: Gallimard. - Díaz Bernal, Juan Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
ReseñaAutor: Michel Foucault (1926-1984)Título: Histoire de la sexualité: Les aveux de la chairEditorial: GallimardAño: 2018